THE ROLE OF THE PRINCIPAL AS A LEADER IN IMPROVING TEACHER PERFORMANCE - herayati herayati (Jurnal Scientia, 2022)
This study aims to describe the role of the principal as a leader in improving teacher performance. The principal is the highest position in the school organization. The principal acts as a school leader and in the school organizational structure his position is at the top. The principal as a leader must be able to provide guidance and supervision, improve the ability of educators, open two-way communication, and delegate tasks. Thus the principal plays a very important role in improving teacher performance. Teacher performance is the result of teacher work that can be achieved by a teacher in educational institutions in accordance with their duties and responsibilities. In the learning process the teacher is seen as having an important role, especially in helping students to develop their potential in cognitive, affective and psychomotor abilities, the teacher also seeks to arouse curiosity, encourage independence and accuracy of intellectual logic, and create conditions for success in learning This value is included in the "Good" category because it is in the 68% -84% interval range. Thus the performance of teachers at the Tangerang Junior High School for the 2020/2021 school year can be said to be with a good interpretation. There is a significant influence between the principal's leadership on the performance of Tangerang Junior High School teachers in the 2020/2021 academic year. This is evidenced by the results of the F test where, the value of F = 26.605 > 4.451 (value Ftable, F(0.05;1.17) = 4.451) and sig = 0.000 < 5% this means Ho is rejected, Ha is accepted, meaning the independent variable leadership the principal has a significant effect on the dependent variable of teacher performance. So in other words, the independent variable of the principal's leadership is able to explain the magnitude of the dependent variable of teacher performance. From the results of this study, it is expected that school principals continuously foster and evaluate the implementation of teacher duties in order to achieve the goals that have been set optimally. Principals and teachers should also maintain a comfortable and safe school climate in order to create a conducive learning atmosphere